THE EFFECTIVENESS OF CONSTRUCTIVE LEARNING ENVIRONMENT MODELS IN LEARNING LISTENING SKILLS TO IMPROVE COLLEGE STUDENT LEARNING OUTCOMES - Naryatmojo, Deby Luriawati; Haryadi, Haryadi; Prasandha, Diyamon (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Objective study this is for know effectiveness of environmental models study constructive in learning skills listen . Method study this use type quantitative quasi experiment (experiment pseudo) with nonequivalent control group design. Study this conducted at Eleven March University as group control and Semarang State University as group experiment with using a learning model environment Study constructive. Instrument study this consists from instrument test and non- test . Instrument the test form test essay college students, meanwhile instrument non-test form interviews, questionnaires, observations. Data analysis techniques are used for know appropriateness instrument study form validity and reliability, for test condition data analysis in the form of normality and homogeneity tests, as well as for test hypothesis using sample t test paired and sample t test independent test. Research result shows the class t test experiment shows the environmental model study constructive proven effective. The results of the t test analysis stated that the average posttest score for the UNS (control) group was 80.25 and the average score group Unnes (experimental ) of 87.19, there is the average difference in data is 6,942. The t-test value is 3.936 and is significant of 0,000. That figure show significant numbers (0.000 < 0.05) are meaningful there is significant difference use of environmental models study constructive to the group experiment more effective with acquisition figure 87.19 compared group control. Therefore that, based on findings research, use of environmental models study constructive in learning skills listen more effective and possible increase results study student.